Antioxidant and Anticancer Activities of Sand Sea Cucumber (Holothuria scabra) Extracts using Wet Rendering Extraction Method - Nunik Gustini; Diah Anggraini Wulandari; Fauzy Rachman; Eris Septiana; Siti Irma Rahmawati; Gita Syahputra; Martha Sari; Masteria Yunovilsa Putra (Jurnal Kimia Sains dan Aplikasi, 2023)
Antioxidant and anticancer activities of sand sea cucumber Holothuria scabra (dried and fresh) extracts were studied. The highest extraction yield of sea cucumber H. scabra (3.9%) was obtained using dried H. scabra at 60oC. The highest antioxidant activity was found in fresh H. scabra extract at 60°C with an IC50 value of 629.89 ± 0.15 µg/mL using the ABTS method, and the highest antioxidant activity by DPPH method was found in dried H. scabra extract at 70°C with an IC50 value of 32017.18 ± 0.82 µg/mL. The best antioxidant activity based on FRAP and TBARS methods was found in fresh H. scabra extracts at 80°C, respectively. The highest total phenol and flavonoid contained in dried H. scabra extract were 317.54 ± 8.91 mg GAE/100 g sample and 247.56 ± 11.70 mg QE/100 g sample. H. scabra extracts inhibited more than 50% of the growth of the MDA-MB-231 cell line at concentrations of 25 and 50 μg/mL except for dried H. scabra extracts at 80°C. Similarly, the extracts showed the highest cytotoxic effect up to 100% at the highest concentration (100 μg/mL) except for dried H. scabra extracts at 70°C and 80°C.